2013
DOI: 10.1534/genetics.113.150292
|View full text |Cite
|
Sign up to set email alerts
|

Population Genetics and Molecular Evolution of DNA Sequences in Transposable Elements. I. A Simulation Framework

Abstract: A population genetic simulation framework is developed to understand the behavior and molecular evolution of DNA sequences of transposable elements. Our model incorporates random transposition and excision of transposable element (TE) copies, two modes of selection against TEs, and degeneration of transpositional activity by point mutations. We first investigated the relationships between the behavior of the copy number of TEs and these parameters. Our results show that when selection is weak, the genome can m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 34 publications
1
6
1
Order By: Relevance
“…1 ). The shorter external branches in V. angularis , compared to those in V. radiata , also suggest lesser activities in V. radiata as was also suggested in simulation studies ( Kijima and Innan 2013 , Navarro-Quezada and Schoen 2002 ).…”
Section: Discussionsupporting
confidence: 68%
“…1 ). The shorter external branches in V. angularis , compared to those in V. radiata , also suggest lesser activities in V. radiata as was also suggested in simulation studies ( Kijima and Innan 2013 , Navarro-Quezada and Schoen 2002 ).…”
Section: Discussionsupporting
confidence: 68%
“…Theoretical investigations have suggested that stronger selection against the deleterious effects of TE insertions results in fewer copies, but also leads to a higher percentage of active elements [ 16 - 18 ]. Inactive (or less active) elements have a lower chance of surviving the selective filter that the host genome presents, possibly winnowing TE diversity over long time periods.…”
Section: Discussionmentioning
confidence: 99%
“…Second, simulation studies suggest that high rates of TE deletion may drive non-neutral sequence evolution by heightening the strength of selection on transpositional activity [63], as the birth rate of new insertions must compensate for the heightened death rate of preexisting insertions for the family to remain viable. If there are fitness impacts on the organism of excessive telomere elongation [64], which additional observations of telomere trimming suggest may be the case [65,66], this heightened selection on transposition may also intensify conflict among the HTTs as they compete for limited space and transposition machinery.…”
Section: Telomere Instability Contributes To the Rapid Evolution Of Hmentioning
confidence: 99%